Non-additive effects of leaf and twig mixtures from different tree species on experimental litter-bed flammability - Weiwei Zhao; Richard S. P. van Logtestijn; Jurgen R. van Hal; Ming Dong; Johannes H. C. Cornelissen (Plant and Soil, 2019)

MALDI-TOF MS meets WGS in a VRE outbreak investigation - S. Schlebusch; G. R. Price; R. L. Gallagher; V. Horton-Szar; L. D. H. Elbourne; P. Griffin; D. J. Venter; S. O. Jensen; S. J. Van Hal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Clinical effectiveness of itraconazole as antifungal prophylaxis in AML patients undergoing intensive chemotherapy in the modern era - C. L. Keighley; P. Manii; S. R. Larsen; S. van Hal (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Bio‐energetics underpins the spatial response of North Sea plaice ( Pleuronectes platessa L.) and sole ( Solea solea L.) to climate change - Lorna R. Teal; Ralf van Hal; Tobias van Kooten; Piet Ruardij; Adriaan D. Rijnsdorp (Global Change Biology, 2012)
Climate change is currently one of the main driving forces behind changes in species distributions, and understanding the mechanisms that underpin macroecological patterns is necessary for a more predictive science. Warming sea water temperatures are expected to drive changes in ectothermic marine species ranges due to their thermal tolerance levels. Here, we develop a mechanistic tool to predict size‐ and season‐specific distributions based on the physiology of the species and the temperature and food conditions in the sea. The effects of climate conditions on physiological‐based habitat utilization was then examined for different size‐classes of two commercially important fish species in the North Sea, plaice, Pleuronectes platessa , and sole, Solea solea . The two species provide an attractive comparison as they differ in their physiology (e.g. preferred temperature range). Combining dynamic energy budget ( DEB ) models with the temperature and food conditions estimated by an ecosystem model ( ERSEM ), allowed spatial differences in potential growth (as a proxy for habitat quality) to be estimated for 2 years with contrasting temperature and food conditions. The resulting habitat quality maps were in broad agreement with observed ontogenetic and seasonal changes in distribution as well as with the recent changes in distribution which could be attributed to an increase in coastal temperatures. Our physiological‐based model provides a powerful tool to explore the effect of climate change on the spatio‐temporal fish dynamics, predict effects of local or broad‐scale environmental changes and provide a physiological basis for observed changes in species distributions.

Tundra in the Rain: Differential Vegetation Responses to Three Years of Experimentally Doubled Summer Precipitation in Siberian Shrub and Swedish Bog Tundra - Frida Keuper; Frans-Jan W. Parmentier; Daan Blok; Peter M. van Bodegom; Ellen Dorrepaal; Jurgen R. van Hal; Richard S. P. van Logtestijn; Rien Aerts (Ambio, 2012)

Divergent composition but similar function of soil food webs of individual plants: plant species and community effects - T. M. Bezemer; M. T. Fountain; J. M. Barea; S. Christensen; S. C. Dekker; H. Duyts; R. van Hal; J. A. Harvey; K. Hedlund; M. Maraun; J. Mikola; A. G. Mladenov; et al. (Ecology, 2010)
Soils are extremely rich in biodiversity, and soil organisms play pivotal roles in supporting terrestrial life, but the role that individual plants and plant communities play in influencing the diversity and functioning of soil food webs remains highly debated. Plants, as primary producers and providers of resources to the soil food web, are of vital importance for the composition, structure, and functioning of soil communities. However, whether natural soil food webs that are completely open to immigration and emigration differ underneath individual plants remains unknown. In a biodiversity restoration experiment we first compared the soil nematode communities of 228 individual plants belonging to eight herbaceous species. We included grass, leguminous, and non‐leguminous species. Each individual plant grew intermingled with other species, but all plant species had a different nematode community. Moreover, nematode communities were more similar when plant individuals were growing in the same as compared to different plant communities, and these effects were most apparent for the groups of bacterivorous, carnivorous, and omnivorous nematodes. Subsequently, we analyzed the composition, structure, and functioning of the complete soil food webs of 58 individual plants, belonging to two of the plant species, Lotus corniculatus (Fabaceae) and Plantago lanceolata (Plantaginaceae). We isolated and identified more than 150 taxa/groups of soil organisms. The soil community composition and structure of the entire food webs were influenced both by the species identity of the plant individual and the surrounding plant community. Unexpectedly, plant identity had the strongest effects on decomposing soil organisms, widely believed to be generalist feeders. In contrast, quantitative food web modeling showed that the composition of the plant community influenced nitrogen mineralization under individual plants, but that plant species identity did not affect nitrogen or carbon mineralization or food web stability. Hence, the composition and structure of entire soil food webs vary at the scale of individual plants and are strongly influenced by the species identity of the plant. However, the ecosystem functions these food webs provide are determined by the identity of the entire plant community.